Study of the Effect of Mowing and Drying on the Lipid Composition of Grass Leaves in Permafrost Ecosystems - Vasiliy V. Nokhsorov; Lyubov V. Dudareva; Natalia V. Semenova; Klim A. Petrov (Agronomy, 2023)
Mowing the plant shoots under hot, sunny, and dry conditions severely traumatizes the entire vegetative body, and the overall life cycle of the plant is altered. The purpose of the present research was to investigate the effects of mowing and drying on lipids, fatty acids (FA), sterols, and the systemic responses in leaves of plant material at three time points (24 h, 72 h, and leaves of new shoots after traumatic mowing in summer (1 July) and those subjected to cold hardening by autumn temperatures in September (aftergrass)) were analyzed for the first time. The leaves of five species of herbaceous plants growing in permafrost ecosystems were analyzed by HPTLC and GC-MS. It was established that fatty acids in the tissues of aftergrass leaves were characterized by higher values of the n-6/n-3 ratio than in summer grasses. It was demonstrated that exposure of leaves for 72 h in natural conditions in summer and at low temperatures in autumn in leaves of aftergrass resulted in significant changes in the composition of membrane phospholipids. The obtained findings indicate that leaves of aftergrass are the most valuable plant raw material in terms of FAs and phytosterols content compared to hay mowed in summer.